Petrografia e aspectos diagenéticos dos arenitos da Formação Corda e da Formação Mosquito, jurássico-cretáceo da bacia do Parnaíba, região de Montes Altos (MA) - GARCIA, Felipe Rudá de Magalhães (2019)
Petrologicalanalysis related to basal siliciclastic rocks of the Upper CretaceousCordaFormation was carried out in theoutcrops andcore samples were collected in the central partofthe Parnaíba Basin, Formosa da Serra Negra and Montes Altos Region, State of Maranhão, Northern Brazil. The petrographic studies were concentrated in the samples collected near of contact with theUpper Jurassic MosquitoFormation that overlaid theCorda Formation. Two types ofsandstones were classified: 1)quartz-arenites,withapproximately 96% ofmonocrystallineandpolycrystallinegrainsofroundedto subroundedquartz; and 2)sublitarenites, composed ofmoderatelysorted and very finegrained sand. Subangularto subroundedgrainsexhibit primary borders modified syntaxial overgrowth. The mineralogyconsists around81% of quartzgenerally showing overgrowth and strongundulatingextinction. Therock fragmentsare the seconddominantcomponent in therock withratio10.5%andare composed of volcanic and pelitic rocks. The feldsparsare represented byplagioclase andmicroclinea lesser extentthan 3%.The grains exhibit predominantly straightcontactsin mostcurvedandless frequently. Secondaryconstituents of therockframeworkare represented by zeolite poiquilotopic, calcite and oxide/hidróxide iron cements. Both types ofsandstonesanalyzed by Xraysdiffraction showed moderate peaks of eoliteprobably the estalbite type. Kaoliniteis predominantin all facies while smectite was observed only indune fieldsdeposits.Kaoliniteindicates the presence ofwater in the system, while theesmectite seems to indicatearid climate consistent with the interpretation of humid desert paleoenvironment of theCordaFormation. The facies of this unit were grouped into fourfacies associations: braided fluvial, sand sheets, dune field and suspensionlobes.The sandstones have experienced the following diagenetic processes: mechanical infiltration of clay,cementation by iron oxidehydroxides and calcite, quartz overgrowth, mechanical compression /chemicalandgeneration of secondary porosity.